Internalization of Muhammad Yamin's character values as a source of character values in civics learning - Hendra, Hendra; Sari, Retno Maya; Sari, Serli Retno (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This research is motivated by the need for a special approach to instill character values. This study aims to analyze the process of internalizing the values of Muhammad Yamin's character as a source of character values in Civics learning. The research was conducted at SMPN 16 Kerinci grade 8 in Civics learning. The research was conducted with a qualitative approach to explore and analyze the internalization of Muhammad Yamin's character values as a source of character values in civics learning at SMPN 16 Kerinci. Data were analyzed using the Miles and Huberman model: data reduction, data presentation, and conclusion drawing. Data credibility was tested with source triangulation. The results showed: (1) The values of Muhammad Yamin's character that are internalized in learning are democratic, integrity, love of reading, nationalism, and tolerance; (2) Internalization of Muhammad Yamin's character values is carried out in three stages, namely planning, implementation, and evaluation; and (3) The internalization process is well implemented. The study's results are expected to reference research on the internalization of character values.